Cultural dimensions of West Indian development: religion and philosophy. - Bisnauth, Dale (1995)
Discusses the need for reflective dialogue on the part of the various religious peoples in the region. Notes that in the struggle for survival which has been the preoccupation of the majority of Caribbean peoples for the better part of their history, religion has served as part of the mechanism for survival, and can in future act as an integrating mechanism for the region.